Formulation Development of Efavirenz TabletsEmploying β Cyclodextrin- PVP K30- SLS: AFactorial Study - K.P.R. Chowdary, A. Naresh (Journal of Applied Pharmaceutical Science)
Efavirenz, a widely prescribed anti retroviral drug belongs to class IΙ under BCSand exhibit low and variable oral bioavailability due to its poor aqueous solubility. Its oralabsorption is dissolution rate limited and it requires enhancement in the solubility anddissolution rate for increasing its oral bioavailability. The objective of the study is to evaluatethe feasibility of formulating efavirenz –βCD– PVP K30/SLS inclusion complexes intotablets and to evaluate the effects of βCD, PVP K30and SLS on the dissolution rate anddissolution efficiency of efavirenz tablets in a 23 factorial study. A comparative evaluationof wet granulation and direct compression methods was made for the preparation of tabletsemploying drug – βCD – PVP K30/ SLS inclusion complexes. Drug – βCD- PVP K30/ SLSinclusion complexes were prepared by kneading method. Tablets each containing 50 mg ofefavirenz were prepared by wet granulation and direct compression methods employingvarious βCD complexes as per 23 factorial design and the tablets were evaluated fordissolution rate and other physical properties. Efavirenz tablets formulated employing dug –βCD – PVP K30/ SLS inclusion complexes and prepared by direct compression methoddisintegrated rapidly when compared to those made by wet granulation method. Efavirenzdissolution was rapid and higher from the tablets formulated employing drug- βCD- PVP K30/or SLS inclusion complexes when compared to the tablets containing efavirenz alone in bothwet granulation and direct compression methods. The individual as well as combined effectsof the three factors involved i.e., βCD ( factor A), PVP K30( factor B) and SLS( factor C)were highly significant (P< 0.01) in enhancing the dissolution rate (K1) and dissolutionefficiency (DE 30) of efavirenz in both wet granulation and direct compression methods.Among the three factors βCD (factor A) gave highest enhancement in the dissolution rate(K1) and dissolution efficiency (DE 30) of efavirenz tablets in both wet granulation and directcompression methods. SLS (factor C) alone gave low dissolution rate in both wet granulationand direct compression methods .Overall direct compression method gave higher dissolutionrates (K1) and dissolution efficiency (DE 30) values than the wet granulation method in all thecases. Combination of βCD with either PVP K30 or SLS or both gave a significantly higherdissolution rate (K1) of efavirenz in both wet granulation and direct compression methods.Hence a combination of βCD with either PVP K30 or SLS or both is recommended toenhance the dissolution rate and efficiency of efavirenz tablets.